Compliance or beyond: Seeking an answer for Environmental, Social, and Governance (ESG) practices of listed companies in Vietnam - Hien Thu Nguyen (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
ESG could be driven by regulation as per the legitimacy view, realized benefits as per stakeholders and resource-based views, or by governance problems as per managerial agency view. This paper examines the motivations driving Environmental, Social, and Governance (ESG) practices among firms in Vietnam. Using a panel data of 833 firm-year observations of listed companies in the VNX-All shares during the period from 2018 to 2023 and using the method to decompose ESG into three separate areas and linking them to the development of regulations, it is found that firms tend to engage in ESG practices primarily to comply with regulations. Specifically, the findings indicate that firms in environmentally sensitive industries, which must implement and disclose their environmental practices, are more committed to ESG initiatives than their peers. The findings imply that ESG compliance is especially prominent for companies subject to regulatory requirements. Further analysis reveals that while ESG practices typically benefit firms, these advantages are not fully realized through mere compliance. Our evidence yields support for both the stakeholder and resource-based views. The study illustrates that going beyond compliance can substantially benefit firms; however, this is not necessarily true for ESG initiatives motivated by managerial agency-driven considerations. The findings have important implications for regulators, investors, and corporate boards in understanding the motivations and identifying mechanisms to enhance ESG toward sustainable development.